Rabies Vaccination and Public Health Insights in the Extended Arabian Gulf and Saudi Arabia: A Systematic Scoping Review - Helal F. Hetta; Khalid S. Albalawi; Amal M. Almalki; Nasser D. Albalawi; Abdulmajeed S. Albalawi; Suleiman M. Al-Atwi; Saleh E. Alatawi; Mousa J. Alharbi; MeshaL F. Albalawi; Ahmad A. Alharbi; Hassabelrasoul Elfadil; Abdullah S. Albalawi; et al. (Diseases)
Background and Aim: This systematic scoping review examines rabies-related incidents, interventions, and post-exposure immunoprophylaxis in the Arabian Gulf region and Saudi Arabian Peninsula. Methods: A comprehensive literature search was conducted in databases including PubMed, Scopus, WoS, MedLine, and Cochrane Library up to July 2024. Studies were included discussing the reported cases of rabies that received the PEP in all countries of the Arabian Gulf, their epidemiological data, the received schedules of vaccination, and their safety. The search was done by using the following terminologies: rabies vaccine, rabies human diploid cell vaccine, vaccine, Saudi Arabia, Bahrain, Iraq, Kuwait, Oman, Qatar, United Arab Emirates, Southwest Asia, Iran, West Asia, Western Asia, Persian Gulf, Arabian Gulf, Gulf of Ajam, Saudi Arabian Peninsula, and The Kingdom of Saudi Arabia. Results: The systematic scoping review included 36 studies, synthesizing findings from diverse research designs, including large-scale cross-sectional studies and case reports, spanning nearly three decades. Findings indicated that young males in urban areas are most at risk for animal bites, predominantly from domestic dogs and cats. While post-exposure prophylaxis (PEP) was generally administered within recommended timeframes, vaccination completion rates varied. Conclusions: The review highlighted gaps in public awareness about rabies risks and prevention. Vaccine safety profiles were generally favorable, with mostly mild-to-moderate side effects reported. The study underscores the need for enhanced public health education, standardized PEP protocols, and a One Health approach to rabies prevention.